Teaching challenges and readiness among Arabic language teachers: merging practicum insights with real-world teaching demands - Che Haron, Sueraya; Senik @ Kamaruddin, Zuraidah; Mustapha, Ariyanti; Ahmat Syafri, Norazman; Mohammed Alobeidani, Mohammed Juma (RSIS International, 2025)
This study investigates the alignment among university training, practicum experiences and the real-world challenges faced by Arabic language teachers, with a particular focus on professional readiness and instructional demands. Drawing on qualitative data from interviews with in-service Arabic language teachers, the findings reveal that the realities encountered during practicum closely mirror those in the teaching profession. However, there is a noticeable disconnect between university-based training and school-based realities. Teachers are expected to demonstrate versatility by assuming multiple roles beyond classroom instruction, including administrative, disciplinary, and community engagement duties. Persistent challenges such as classroom management, mixed-ability teaching, limited teaching resources, and uneven access to digital tools continue to affect both novice and experienced teachers. Furthermore, the study highlights institutional barriers, including school politics and a lack of emotional support structures, which often go unaddressed in teacher training programs. The findings underscore the need for teacher education programs to adopt a holistic and realistic approach; one that prepares future Arabic language teachers not only in pedagogy and content, but also in emotional resilience, digital literacy, and institutional navigation. This paper concludes with recommendations for enhancing teacher preparation programs to better support professional integration and long-term teacher effectiveness.